2005
DOI: 10.1161/circulationaha.104.529628
|View full text |Cite|
|
Sign up to set email alerts
|

Headaches and the Treatment of Blood Pressure

Abstract: Background-Uncertainty exists over whether blood pressure-lowering drugs prevent headache. Methods and Results-A meta-analysis was carried out of the 94 randomized placebo-controlled trials of 4 different classes of blood pressure-lowering drugs (thiazides, ␤-blockers, ACE inhibitors, and angiotensin II receptor antagonists) in fixed doses in which data on headache were reported. There were 17 641 participants who were allocated blood pressure-lowering drugs and 6603 who were allocated placebo. Treatment lower… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
23
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(27 citation statements)
references
References 37 publications
1
23
1
Order By: Relevance
“…All previous studies addressing this issue had important limitations, which left this as a medical impasse. The same seems to occur in a recent publication by Law et al 1 in Circulation. After a judicious selection of 94 randomized trials with 4 classes of blood pressure-lowering drugs at fixed doses, the authors concluded that all classes reduce the prevalence of headache by one third, suggesting that high blood pressure is a cause of headache.…”
Section: To the Editorsupporting
confidence: 76%
See 2 more Smart Citations
“…All previous studies addressing this issue had important limitations, which left this as a medical impasse. The same seems to occur in a recent publication by Law et al 1 in Circulation. After a judicious selection of 94 randomized trials with 4 classes of blood pressure-lowering drugs at fixed doses, the authors concluded that all classes reduce the prevalence of headache by one third, suggesting that high blood pressure is a cause of headache.…”
Section: To the Editorsupporting
confidence: 76%
“…The number of patients treated with a symptomatic drug who reached discharge criteria (patients reporting no symptoms, systolic pressure Ͻ180 mm Hg, and diastolic pressure Ͻ110 mm Hg) was similar to that of patients treated with antihypertensive drugs. These results no longer support the idea that headache could be a cause of high blood pressure and not a consequence, as suggested by Law et al 1 People with hypertension need treatment for hypertension, and people with headache need treatment for their headaches with prophylactic drugs, which could include antihypertensive drugs with prophylactic properties, or analgesics. Most of the time, analgesics would be a better, cheaper, and probably safer option.…”
Section: To the Editorcontrasting
confidence: 55%
See 1 more Smart Citation
“…
We recently reported a meta-analysis of 94 randomized placebo-controlled trials of blood pressure-lowering drugs in which the prevalence of headache was reported [1]. On average, one-third fewer people reported headache in the treated groups than in the placebo groups [odds ratio (OR) 0.67; 95% confidence interval (CI) 0.61, 0.74; P < 0.001].
…”
mentioning
confidence: 99%
“…We here present the results on calcium channel blockers and headache, the net effect according to dose, from our meta-analysis of randomized trials [1,2].…”
mentioning
confidence: 99%